String theory in a nutshell - Kiritsis Elias (Princeton Princeton Univ Press, 2007)
This book has a good selection of material, starting from basics and moving into classic and modern topics. Overall the book nicely covers the major advances of the last ten years, including (non-perturbative) string dualities, black hole physics, AdS/CF
Keywords: String models